Adding value and meaning to coheating tests. Issue 4 (2014) - Anne Stafford; David Johnston; Dominic Miles‐Shenton; David Farmer; Matthew Brooke‐Peat; Chris Gorse
<x xml:space="preserve"> Abstract </x> Purpose – The coheating test is the standard method of measuring the heat loss coefficient of a building, but to be useful the test requires careful and thoughtful execution. Testing should take place in the context of additional investigations in order to achieve a good understanding of the building and a qualitative and (if possible) quantitative understanding of the reasons for any performance shortfall. The paper aims to discuss these issues. Design/methodology/approach – Leeds Metropolitan University has more than 20 years of experience in coheating testing. This experience is drawn upon to discuss practical factors which can affect the outcome, together with supporting tests and investigations which are often necessary in order to fully understand the results. Findings – If testing is approached using coheating as part of a suite of investigations, a much deeper understanding of the test building results. In some cases it is possible to identify and quantify the contributions of different factors which result in an overall performance shortfall. Practical implications – Although it is not practicable to use a fully investigative approach for large scale routine quality assurance, it is extremely useful for purposes such as validating other testing procedures, in‐depth study of prototypes or detailed investigations where problems are known to exist. Social implications – Successful building performance testing is a vital tool to achieve energy saving targets. Originality/value – The approach discussed clarifies some of the technical pitfalls which may be encountered in the execution of coheating tests and points to ways in which the maximum value can be extracted from the test period, leading to a meaningful analysis of the building's overall thermal performance.